The language and thought of the child - Piaget, Jean. (New York : Routledge, Kegan Paul Ltd., 1926)
One of the most salient and inspirational figures in psychological and educational research of the 20th century, Piaget was also prolific, authoring or editing over 80 books and numerous papers. This volume is the sixth in a set of nine which reproduce his original texts.
Includes index.
Keywords: Child development; Children -- Language; Psychology -- Child